ISOSTASY OF ANTARCTICA. - Ushakov,S. A.; Frolov,A. I. (1967)
Because of the complexity of isostatic anomaly computations, the conclusion on the isostatic state of Antarctica was originally drawn by averaged anomalies with a free-air reduction. However, B. A. Andreyev drew the conclusion that at the center of Antarctica one can expect to discover intensive negative isostatic anomalies of the order of 80 mgals. In this article the authors independently and by different methods attempted to find answers to the given conclusions. (Author) Izostaziya Antarktidy, trans. of Akademiya Nauk SSSR. Doklady, v160 n4 p819-22 1965.